Febrile neutropenia management in pediatric cancer patients at Ethiopian Tertiary Care Teaching Hospital - Mohammed, Husnia Bedewi (BMC Res Notes, 2019)
OBJECTIVE: This study aimed at assessing the management practice of febrile neutropenia (FN) in pediatric cancer patients at Tikur Anbessa Specialized Hospital (TASH), Ethiopia by reviewing patients’ charts from 135 participants retrospectively. Data was entered into Epi-info 7 and exported to SPSS 20 for analysis. RESULTS: Empiric antibiotics therapy (EAT) was given to all patients in which ceftriaxone with gentamycin constituted of 71.8% followed by ceftriaxone monotherapy. EATs were converted to others in 20 (14.8%) and 2 (1.5%) patients for the first and second times respectively, mainly based on poor clinical response without conducting culture and sensitivity tests. These tests were done only for 13 (9.6%) participants and growth was seen in 5 patients; and definitive therapy was given for 2 patients. ANC value was above 500 cell/mm(3) in 80.7% of patients and 98.5% of study participants were afebrile after completion FN treatment. Most of them (70.4%) were treated for FN and 7 of patients died due to all case mortality. The hospital should not rely mainly only on ceftriaxone with gentamycin as EAT and should do culture and sensitivity test to optimize therapy based on susceptibility result before conversion and modification of therapy in management of FN.